Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Implicit Differentiation

  • Page ID
    624
  • [ "article:topic" ]

    \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

    \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

    Implicit and Explicit Functions

    An explicit function is an function expressed as y = f(x) such as

    \[  y = \text{sin}\; x \]

    y is defined implicitly if both x and y occur on the same side of the equation such as

    \[ x^2 + y^2 = 4 \]

    we can think of y as function of x and write:

    \[ x^2 + y(x)^2 = 4\]

    Implicit Differentiation

    To find dy/dx, we proceed as follows:

    1. Take d/dx of both sides of the equation remembering to multiply by y' each time you see a y term.
    2. Solve for y'

    Example
    Find dy/dx implicitly for the circle

    \[   x^2 + y^2 = 4 \]

    Solution

    1. d/dx (x2 + y2)  =  d/dx (4)

      or

        2x + 2yy'  =  0

    2. Solving for y, we get

              2yy'  =  -2x

              y'  =  -2x/2y

              y'  =  -x/y


    Example: 

    Find y' at (4,2) if

    \[ xy + \dfrac{x}{y}  =  10\]

    Solution: 

    1. \[ (xy)' + \left(\dfrac{x}{y}\right)' = (5)' \]
      Using the product rule and the quotient rule we have

    2. \[ xy' + y + \dfrac{y - xy'}{ y^2} =  0 \]

    3. Now plugging in x = 4 and y = 2,

                               2 - 4y'
              4y' + 2 +                =  0
                                  22
         

              16y' + 8 + 2 - 4y' = 0         Multiply both sides by 4

              12y' + 10  =  0

              12y' = -10

              y' = -5/6

    Exercises

    1. Let    
      \[ 3x^2 - y^3  = 4x \text{cos}\; x + y^2 \]
      Find dy/dx

    2. Find dy/dx at (-1,1) if
      \[  (x + y)^3 = x^3 + y^3  \]

    3. Find dy/dx if
      \[ x^2 + 3xy + y^2 = 1\]

    4. Find y'' if
      \[ x^2 - y^2 = 4\]

    Larry Green (Lake Tahoe Community College)